The impact of loneliness on self-rated health symptoms among victimized school children - Løhre Audhild (BMC, 2012)
Abstract Background Loneliness is associated with peer victimization, and the two adverse experiences are both related to ill health in childhood and adolescence. There is, however, a lack of knowledge on the importance of loneliness among victimized children. Therefore, possible modifying effects of loneliness on victimized school children's self-rated health were assessed. Methods A population based cross-section study included 419 children in grades 1-10 from five schools. The prevalence of loneliness and victimization across grades was analyzed by linear test for trend, and associations of the adverse experiences with four health symptoms (sadness, anxiety, stomach ache, and headache) were estimated by logistic regression. Results In crude regression analysis, both victimization and loneliness showed positive associations with all the four health symptoms. However, in multivariable analysis, the associations of victimization with health symptoms were fully attenuated except for headache. In contrast, loneliness retained about the same strength of associations in the multivariable analysis as in the crude analysis. More detailed analyses demonstrated that children who reported both victimization and loneliness had three to seven times higher prevalence of health symptoms compared to children who reported neither victimization nor loneliness (the reference group). Rather surprisingly, victimized children who reported no loneliness did not have any higher prevalence of health symptoms than the reference group, whereas lonely children without experiences of victimization had almost the same prevalence of health symptoms (except for stomach ache) as children who were both victimized and lonely. Conclusions Adverse effects of loneliness need to be highlighted, and for victimized children, experiences of loneliness may be an especially harsh risk factor related to ill health.